MODERNISASI PENDIDIKAN ISLAM: LATAR BELAKANG, CAKUPAN DAN POLA - Rustam Ependi (Jurnal Al-Fatih, 2019)
Radicalism and Liberalism Thought turned out to have an Influence on the Development of Islamic Education in Indonesia. In the case of the Islamic Education movement Indonesian students may be the most important contemporary channel for Islamist ideas from the Middle East to Indonesia. Thousands of Indonesian students receive scholarships from Middle Eastern Islamic countries to study at leading universities. While Liberalism also has an influence in the development of Islamic education in Indonesia with an Indonesian nuance. The concepts and ideas about Islamic education are clearly seen in his ideas on the renewal of Islamic education, in aspects of Islamic education, starting from the vision, mission, goals, curriculum, management and leadership.